Does American democracy still work? - Wolfe, Alan, 1942- (Future of American democracy., 2006)
The past few decades have brought a shift in the nature of American democracy, an alarming shift that threatens such liberal democratic values as respect for pluralism, acceptance of the separation of powers, and recognition of the rights of opposition parties. In this insightful book, political scientist Alan Wolfe identifies the current political conditions that endanger the quality of our democracy. He describes how politics has changed, and he calls for a democracy protection movement designed to preserve our political traditions not unlike the environmental protection movement's efforts to safeguard the natural world. Voters who know little about issues, leaders who bend rules with little fear of reprisal, and political parties that are losing the ability to mobilize citizens have all contributed to a worrisome new politics of democracy, Wolfe argues. He offers a brilliant analysis of how religion and morality have replaced political and economic self-interest as guiding principles, and how a dangerous populism promotes a radical form of elitism. Without laying blame on one party or ideology and without claiming that matters will improve with one party or the other in office, Wolfe instead suggests that Americans need to understand the danger their own indifference poses and take political matters more seriously.